1997
DOI: 10.1161/01.str.28.3.588
|View full text |Cite
|
Sign up to set email alerts
|

Bigated Transcranial Doppler for the Detection of Clinically Silent Circulating Emboli in Normal Persons and Patients With Prosthetic Cardiac Valves

Abstract: Bigated Doppler adds a new dimension to the definition and detection of microembolic signals. It constitutes an important step forward toward automatic screening of stroke-prone patients. Assessing on-line periods of interest during the recording and going over the recorded data again off-line helps to save time for the discrimination of embolic signals from both the normal Doppler spectrum background and artifacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 19 publications
0
31
1
2
Order By: Relevance
“…[13][14][15][16][17][18][19][20][21][22][23][24] In our study, the signals were reviewed by 2 observers, and for inclusion, both observers had to agree that the signal was a true embolic signal. The following definition for embolic signals was used: (1) typical visible, (2) short duration, (3) high-intensity signal, (4) within the Doppler spectrum, and (5) occurring at random within the cardiac cycle.…”
Section: Role Of Human Expertsmentioning
confidence: 99%
See 3 more Smart Citations
“…[13][14][15][16][17][18][19][20][21][22][23][24] In our study, the signals were reviewed by 2 observers, and for inclusion, both observers had to agree that the signal was a true embolic signal. The following definition for embolic signals was used: (1) typical visible, (2) short duration, (3) high-intensity signal, (4) within the Doppler spectrum, and (5) occurring at random within the cardiac cycle.…”
Section: Role Of Human Expertsmentioning
confidence: 99%
“…They did not have cardiac or cerebrovascular disease. In them, we performed a 6-minute series of provoked artifacts, 16 including movement of the probe, coughing, sneezing, and head rotation.…”
Section: Artifactsmentioning
confidence: 99%
See 2 more Smart Citations
“…there are two possible ways of determining the detection threshold of microemboli in decibels for a given device: either by defining the range of spontaneous intensity fluctuations within the doppler signals of normal controls, or by defining fluctuations on a case-by-case basis during emboli-free periods (39,42). Spencer et al (42) reported the characteristic features of embolic signals to be transient (lasting 0.01-0.1 s), an audible chirping quality caused by their being centered on one frequency, and an intensity of up to 40 dB greater than that of the doppler signal from blood alone. One should keep in mind that not all the HItS are produced by microemboli.…”
Section: Generation Detection and Prevention Of Gaseous Microembolimentioning
confidence: 99%